Latent fragility: Conditioning banks' joint probability of default on the financial cycle - Paul Bochmann; Paul Hiebert; Yves Schüler; Miguel Segoviano (European Central Bank (ECB), 2022)
We propose the CoJPoD, a novel framework explicitly linking the cross-sectional and cyclical dimensions of systemic risk. In this framework, banking sector distress in the form of the joint probability of default of financial intermediaries (reflecting contagion from both direct and indirect interconnectedness) is conditioned on the financial cycle (reflecting the buildup and unwinding of system-wide balance sheet leverage). An empirical application to large systemic banks in the euro area, US and UK illustrates how the unravelling of excess leverage can magnify banking sector distress. Capturing this dependence of banking sector distress on prevailing financial imbalances can enhance risk surveillance and stress testing alike. An empirical signaling exercise confirms that the CoJPoD outperforms the individual capacity of either its unconditional counterpart or the financial cycle in signaling financial crises - particularly around their onset - suggesting scope to increase the precision with which macroprudential policies are calibrated.
Keywords: C19; C54; E58; G01; G21; 330; Systemic Risk; Financial Crises; Portfolio Credit Risk; Multivariate DensityOptimization; Financial Cycle